Catatan pinggir sejarah Aceh : perdagangan, diplomasi, dan perjuangan rakyat - Madjid, Dien (Jakarta : Yayasan Pustaka Obor Indonesia, 2014)
On history of Nanggroe Aceh Darussalam.
Includes bibliographical references (page 384-391) and index.
In Indonesian.
Keywords: Nanggroe Aceh Darussalam (Indonesia) -- History; Aceh (Indonesia) -- History; Aceh (Indonesia) -- History -- Politics and government